2014
DOI: 10.1007/s00268-014-2706-9
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Red Cell Distribution Width in Diagnosing Acute Mesenteric Ischemia in Patients with Abdominal Pain

Abstract: The RDW on admission is of marginal help to diagnose AMI among patients with abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
0
25
1
Order By: Relevance
“…[2,11] In an earlier study [25] of RDW in the context of diagnosing AMI, cut-off value, sensitivity, and specificity were 15.04%, 40.8%, and 81.2%, respectively. Another study [26] found that the AUC for RDW was 0.713, and that the cut-off value was 14.85%.…”
Section: Discussionmentioning
confidence: 96%
“…[2,11] In an earlier study [25] of RDW in the context of diagnosing AMI, cut-off value, sensitivity, and specificity were 15.04%, 40.8%, and 81.2%, respectively. Another study [26] found that the AUC for RDW was 0.713, and that the cut-off value was 14.85%.…”
Section: Discussionmentioning
confidence: 96%
“…Early recognition and management is imperative to prevent the related complications. Kisaoglu et al[71] carried a cross-sectional study by comparing AMI patients ( n = 49) with patients with abdominal pain who did not undergo surgery ( n = 110). A RDW value of 15.4% had 0.41 sensitivity and 0.81 specificity for identifying AMI patients after adjustment for anemia.…”
Section: Rdw and Other Digestive Disordersmentioning
confidence: 99%
“…A RDW value of 15.4% had 0.41 sensitivity and 0.81 specificity for identifying AMI patients after adjustment for anemia. However, no correlation was found between RDW and size of ischemia or mortality[71]. Bilgiç et al[72] investigated the preoperative RDW value in a retrospective cohort of 61 patients with AMI, and found that increased RDW predicted both the extent of necrosis and mortality.…”
Section: Rdw and Other Digestive Disordersmentioning
confidence: 99%
“…Red blood cell distribution width (RDW) is a vascular disease marker used in many diseases with ischemia including ischemic coronary artery, mesenteric ischemia, peripheral arterial disease and neurovascular disease [17][18][19] .In a study of 456 we found that inflammatory marker RDW values were higher at the first emergency admission in the amputated group than in the other group. We think that this gives an idea in terms of predicting amputation.…”
Section: Discussionmentioning
confidence: 99%